Johnny Cash the life - Hilburn, Robert (New York Brown and Company, 2013)
In this, the definitive biography of an American legend, Robert Hilburn conveys the unvarnished truth about a musical superstar. Johnny Cash's extraordinary career stretched from his days at Sun Records with Elvis Presley and Jerry Lee Lewis to the remarkable creative last hurrah, at age 69, that resulted in the brave, moving "Hurt" video.
Includes bibliographical references (pages 646-663), discography (pages 639-644), filmography (pages 644-645) and index.
Keywords: Cash, Johnny